MO574MINERAL AND BONE DISORDERS CHANGES IN RENAL TRANSPLANTED PATIENTS. (29th May 2021) - Ferreira, Ana Carina; Mendes, Marco; Silva, Cecília; Cotovio, Patrícia; Aires, Inês; Navarro, David; Caeiro, Fernando; Ramos, Rúben; Salvador, Rute; Correia, Bruna; Cabral, Guadalupe; Nolasco, Fernando; et al.
Abstract: Background and Aims: Successful renal transplant restores many physiologic abnormalities, including improvement of chronic kidney disease- mineral and bone disorder (CKD-MBD) syndrome. The primary aims of this study were: analyse the changes and evolution of the 3 components of CKD-MBD pre and 1 year post renal transplantation: the mineral abnormalities, the bone disorders and the vascular calcifications; and to correlate fibroblast grow factor 23 (FGF23), klotho and sclerostin serum levels with bone histomorphometric parameters and CV disease. The secondary aims were to study the evolution of other bone related parameters and correlate those with bone biopsies data, as well as to validate Adragão vascular calcification score in a population of renal transplant patients. Method: We performed a prospective cohort study of a consecutive sample of de novo single renal transplanted patients in our unit. At inclusion, demographic, clinical and transplant-related data were collected, X-ray of the pelvis and hands (for Adragão score) and echocardiographic findings were recorded. All patients were submitted to a bone biopsy and laboratorial evaluation at baseline (time 0 – T0). Patients were followed for 12 months (time 1 – T1), after which performed laboratorial evaluation, a 2 nd bone biopsy, echocardiogram, X-ray of pelvis and hands, bone densitometry and non-contrast cardiac CT (Agatston score). Continuous variables are presented as medians and categorical variables as frequencies. Differences between T0 and T1 were accessed by Wilcoxon matched-pairs test and paired McNemar test. Correlations between bone histomorphometric findings and severity of vascular calcifications with demographic and laboratorial parameters were obtained with Wilcoxon rank-sum test or Kruskall Wallis test. STATA software was used and p < 0.05 was considered statistically significant. Results: We recruited 84 patients in a 28 month-period. At the end of 12 months, 69 patients performed a 2 nd evaluation. Median age 53 years, 48 men, 53 caucasian, median dialysis vintage 55 months. We observe a significant reduction on phosphorus, magnesium, PTH, calcitonin, sclerostin, bone alkaline phosphatase and FGF23. Both calcium and alpha-klotho serum levels increase, with no significant changes in vitamin D levels. 68% of the patients presented renal osteodystrophy at the 2 nd bone biopsy, and we observed a significant increase in the development of low turnover bone disorder, with no major changes in volume or mineralization. Changes in alpha-klotho, bAP and sclerostin (from T0 to T1) were important determinants of changes in turnover, mineralization and volume, respectively. Despite not being statistically significant, we were able to observe an improvement in the cortical bone porosity. Vascular calcifications and echocardiographic findings weren't different comparing to the baseline (Median Adragão score was 1 in both evaluations, and valve calcifications were present in 22% and 23% of patients, with no changes in LVMI). The median Agatston score was 48.5, being the median adjusted percentile of 82%. FGF23 and sclerostin were found to be independent risk factors for extra-osseous calcifications, as well as low bone volume, cortical porosity and osteoid volume. Adragão score and valve calcifications correlated well with the increased severity of coronary calcifications determined by Agatston score (absolute and percentile). Conclusion: In conclusion, renal transplantation improves two of the three components of CKD-MBD (biochemical and bone disorders), slowing the progression of vascular calcifications. FGF23, sclerostin and bAP seemed to be key parameters in understanding the bone changes observed in post transplant period, and these hormones also interfere with extra osseous calcification severity. Adragão score seems to be a good tool to access vascular calcifications in renal transplanted patients.